Absolute change in fasting plasma glucose over 12 months is associated with 2-year and 5-year major adverse cardiovascular events in patients with drug-eluting stent implants. (20th January 2015) - Kang, Dong Oh; Seo, Hong Seog; Choi, Byung Geol; Lee, Eunmi; Kim, Ji Park; Lee, Sun Ki; Im, Sung Il; Na, Jin Oh; Choi, Cheol Ung; Lim, Hong Euy; Kim, Jin Won; Kim, Eung Ju; et al.
Abstract: Background: Major adverse cardiovascular events (MACEs) in patients with or without cardiovascular disease (CVD) are greatly affected by various factors associated with metabolism and inflammation. Objective: To determine which clinical parameters at treatment are associated with the development of 2-year and 5-year MACEs in high-risk patients with CVD who have undergone drug-eluting stent (DES) implantation. Method: The present study involved a total of 432 patients who underwent percutaneous coronary intervention with DES. Variables representing the average and absolute amount of change in clinical parameters over the 12-month follow-up were assessed for association with 2-year and 5-year development of MACE. The study population was divided into quartiles for the variable showing the highest correlation to MACE development. Estimated incidence of 2-year and 5-year MACEs for each of the quartiles was determined by survival curve analysis, and subgroup analysis was performed for patients with diabetes and statin users. Results: Absolute change in fasting plasma glucose (FPG) over 12 months showed the highest correlation with 2-year and 5-year MACE development. The estimated incidence of MACE increased with increasing quartiles for absolute change in FPG. The association between absolute change in FPG and MACE development exhibited a stronger relationship for the specific subgroups of patients with diabetes and statin users. Increases and decreases in FPG had a comparable contribution to MACE development. Conclusion: A greater absolute change in FPG over 12 months post-PCI is an independent risk factor for 2-year and 5-year MACE development in DES-implanted patients, especially in the diabetes and statin users.